DEVELOPMENT OF EXPERIMENTAL TESTING SYSTEM AND PERFORMANCE MEASUREMENT OF SMALL TURBOJET ENGINE âOLYMPUSâ - Yuliartha, I.G.K Adhi; Hartono, Firman; Sardjadi, Djoko (Mesin, 2008)
This paper describes the development of experimental testing system and performance measurement of small turbojet engine âOlympusâ manufactured by AMT Netherlands. Variables that measured in the measurement are turbine exit gas temperature, fuel and air mass flow, compressor rotational speed, and thrust produced. In this testing, the thrust generated by the engine is measured using bending beam load cell that completed with four strain gauge (each load cell completed with two strain gauge). Strain gauge used in this testing is manufactured by Measurement Group, Inc with gauge factor 2.095 Â± 0.5%. Air flow is measured by using Pitot tube which is installed in 400 mm long and 107 mm diameter inlet pipe. Measurement sensor of the Thermocouple, which is used to measure turbine exit gas temperature, and tachometer, which is used to measure compressor rotational speed, are connected to electronic control unit and displayed in engine data terminal. Fuel flow is measured byÂ  using digital weight (1 gram resolution) and stopwatch. Fuel consumption at one time interval is recorded manually. The engine revolution was varied from 37000 RPM to 105000 RPM with 10000 RPM interval step. Measurement data are then corrected to get the results on standard pressure and temperature condition. Good agreement between the experiment result and data from references shows that the testing system works as expected.